Analysis of Indonesian buffer zone location selection in anticipating an increase in conflict escalation in the Indo-Pacific region - Moreta, Yos Aru; Suharyo, Okol Sri; Purnomo, Joko; Susilo, A.K. (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Buffer zones have a strategic role in managing conflict. Properly determining a buffer zone can help reduce tensions between countries, prevent conflict escalation and provide time and space for the countries involved in diplomacy. In the context of Indonesia, as a large country in the Indo-Pacific region, determining the Indonesian Buffer Zone (IBZ) will have significant implications for regional and global security. Determinations must consider national interests and state security, while on the other hand, it is necessary to consider the interests of neighboring countries and maintain good relations. Therefore, it is important to identify these challenges and see opportunities for multilateral collaboration in determining the Indonesian Buffer Zone. In this research, the author intends to identify and determine perceptions of Indonesia's outer islands, which will be used as buffer zones using the Delphi method. In the next stage, the author will identify the criteria and sub-criteria for Indonesia's outermost islands in the Indo-Pacific Region as well as obtain ranking priorities using the Analytic Network Process (ANP) approach in developing the Indonesian Buffer Zone, so that analysis can be carried out to determine the right strategy for island development the chosen. Where, later the island area selected as the Indonesian buffer zone can be developed and utilized properly and appropriately. Furthermore, in the next stage, the author uses the Game Theory method to describe the comparison of capabilities and threat interactions between the buffer zone of selected outer islands in Indonesia compared to the buffer zone or military bases of countries from the BRICS and AUKUS alliances that have interests in the Indo-Pacific Region. In this research, it is assumed that the two defense pacts have implemented policies or strategies in this game in the context of developing their military strength in the Indo-Pacific Region. So, it is hoped that Indonesia, as the third player, can anticipate appropriate strategies and policies to maintain the stability of the Indo-Pacific Region.